Analisis Profitabilitas Pada Perusahaan Merger dan Akuisisi Yang Terdaftar di Jakarta Islamic Index - Hasibuan, Hesti Aryani; Nurlaila, Nurlaila; Nasution, Juliana (LPPM Universitas Labuhanbatu, 2023)
: This study aims to determine whether there are differences in the profitability of companies before and after mergers and acquisitions in companies listed in the Jakarta Islamic Index by analyzing the Net Profit Margin (NPM), Return on assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM) of companies before and after mergers and acquisitions. This research method is quantitative comparative. The population of this study is companies that conduct mergers and acquisitions in the Jakarta Islamic Index. The total number of samples found was a total of 27 enterprises. Using documentation techniques in the form of secondary data.Â The data analysis technique of this study used a comparative statistical test analysis of two samples. Testing was conducted using SPSS software version 25. The results showed that (I) there was no difference in the company's npm (Net Profit Margin) before and after the merger and Acquisition (ii) there was no difference in the company'S ROA (Return on assets) before and after the merger and Acquisition (iii) there was no difference in the company'S ROE (Return on Equity) before and after the merger and acquisition (iv) there was no difference in the company'S GPM (Gross Profit Margin) before and after the merger and acquisition.